1991
DOI: 10.1002/bdd.2510120202
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oral diltiazem and five of its metabolites in patients with chronic renal failure

Abstract: The pharmacokinetics of oral diltiazem were studied in 10 patients with chronic renal failure not requiring dialysis and in five healthy volunteers after a single dose of 120 mg. We found that patients with chronic renal failure had lower amounts of unchanged diltiazem and of its main metabolite (MA) in urine and a trend to have slightly higher values of plasma concentration. Since the terminal elimination phase is not affected by chronic renal failure we conclude that this trend is probably the result of alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, it is important to emphasize that these results were derived from the administration of a single oral dose of short-acting diltiazem in a small sample of individuals with severe renal impairment. Later investigations [6] showed that patients with chronic renal failure had increased plasma levels of diltiazem and its 5 main metabolites as compared with non-renal failure patients. …”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to emphasize that these results were derived from the administration of a single oral dose of short-acting diltiazem in a small sample of individuals with severe renal impairment. Later investigations [6] showed that patients with chronic renal failure had increased plasma levels of diltiazem and its 5 main metabolites as compared with non-renal failure patients. …”
Section: Discussionmentioning
confidence: 99%